THE ANALYSIS OF CROWE HOWARTH THEORY TO ELUCIDATE FRAUD FACTORS IN THE ACADEMIC SECTOR - Alpiansah, Restu; Fitriyah, Nur (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Ensuring the attainment of Social Development Goals (SDGs) in the education sector necessitates equipping university students with the necessary skills and qualities to become effective leaders with strong moral principles. The character of students, particularly those in financial majors, can have a significant impact on the quality and integrity of the future human resources in the financial sector. The fraud in the academic sector should not be ignored because it can be a challenge for SDG’s programme. This research aims to find out the influence of the fraud Pentagon’s dimensions/ Crowe’s theory, namely academic pressure, opportunity, rationalisation, competence, and arrogance, on academic students’ dishonesty. The type of research used in this study is quantitative research. The research design in this study is ex post facto. The data in this research is primary data collected with the use of the questionnaire survey, tested with the SmartPLS analysis tool. The result explains that students commit academic fraud supported by academic pressure, the opportunity to conduct the fraud, and the competence to make a strategy to conduct academic dishonesty. Meanwhile, rationalisation and arrogance have no influence on academic students’ dishonesty. We propose the following recommendation to the parties concerned: for education practitioners, this study provides valuable information considering the impact of pressure, opportunity, rationalisation, competence, and arrogance on academic dishonesty behaviour, devising better letter methods or rules to minimise academic fraud among students, especially for online learning and examinations. This study empirically confirms that the fraud pentagon dimension factors influenced 71.1% of academic students’ dishonesty. Meanwhile, the rest was caused by other factors.